Studying protein degradation pathways in vivo using a cranial window-based approach - Unni, Vivek K.; Ebrahimi-Fakhari, Darius; Vanderburg, Charles R.; McLean, Pamela J.; Hyman, Bradley T. (Methods, 2011)
Understanding how specific proteins are degraded by neurons in living animals is a fundamental question with relevance to many neurodegenerative diseases. Dysfunction in the ubiquitin-proteasome system (UPS) specifically has been implicated in several important neurodegenerative diseases including Alzheimer’s Disease, Parkinson’s Disease, and amyotrophic lateral sclerosis. Research in this area has been limited by the fact that many inhibitors of the UPS given systemically do not cross the blood-brain barrier (BBB) in appreciable levels. This limits the ability to easily test in vivo specific hypotheses generated in reduced systems, like brain slice or dissociated cell culture, about whether the UPS may degrade a particular protein of interest. Although several techniques including intracerebral application via direct syringe injection, catheter-pump systems and drug-eluting beads are available to introduce BBB-impermeant drugs into brain they each have certain limitations and new approaches could provide further insights into this problem. In order to test the role of the UPS in protein degradation in vivo we have developed a strategy to treat mouse cortex with the UPS inhibitor clasto-lactacystin beta-lactone (CLBL) via a “cranial window” and recover the treated tissue for immunoblot analysis. This approach can be used in several different cranial window configurations including single window and double hemi-window arrangements that are tailored for different applications. We have also developed two different strategies for recovering treated cortical tissue including a vibratome/laser capture microscopy (LCM)-based and a vibratome only-based approach, each with its own specific advantages. We have documented UPS inhibition >600μm deep into the cortex with this strategy. This set of techniques in the living mammalian brain is complementary to previously developed approaches and extends the repertoire of tools that can be used to the study protein degradation pathways relevant to neurodegenerative disease.
Erstmals am 25. Dezember 2010 online veröffentlicht
Gesehen am 01.12.2022